CRITERIA OF LITERATURE AND CREATIVITY - Bhagat, Jitendra Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Literature is an expression of thoughts and feelings, and also an artistic creation. Various criteria have been set for the evaluation of literature which test the quality of a work, help in highlighting its impact and aesthetics. On the other hand, creativity is the basic element of literature, which gives it novelty and originality as well as a unique style of expression. In this way, creation and criticism are related to each other. Literary creation and the criteria for its evaluation have always been controversial. Creativity is an independent process which is created by the writer's own individual consciousness. On the other hand, critical criteria are often created from social, cultural and theoretical framework. The tension between these two reflects the dynamism of literature. Criteria are in a way those criteria on the basis of which the literary quality, quality and impact of a work are assessed. In traditional norms, Rasa Siddhanta (Bharat Muni), Dhvani Siddhanta (Anandvardhana), Riti, Alankar, Vakrokti etc. are discussed. Modern norms are formed from realism, progressivism, experimentalism, new writing, aesthetics etc. Contemporary norms are based on sensitivity towards gender, Dalit discourse, environment etc. Creativity is basically uncontrolled, original and personal, whereas norms are objective, collective and theoretical. Due to this, conflicts arise many times. To become "literary", the creator feels compelled to follow some rules, due to which his natural expression may get affected, hence Agyeya has also criticized it in the preface of Doosra Saptak. Chhayavadi poets were also accused of 'ambiguity' in the beginning. They also had to face criticism from Shukla ji. No norm is perfect. The work which seems 'unliterary' today, can become a classic tomorrow. When Premchand was writing fiction fluently, his novels were considered to be of the 'ordinary' category, but today they are the priceless heritage of Hindi.